Analysis of T-cell responses in cattle immunized against heartwater by vaccination with killed elementary bodies of Cowdria ruminantium - Totte, P.; McKeever, Declan J.; Martínez, D.; Bensaid, A. (1997)
Cattle were successfully immunized against heartwater with a lysate of Cowdria ruminantium formulated in Freund's adjuvant. Vaccinated animals proved fully resistant to virulent challenge 3 and 10 months after vaccination. For the first time a helper T lymphocyte response to Cowdria antigens was observed and characterized. Cowdria-specific T-cell lines generated from vaccinated animals by in vitro restimulation with Cowdria lysates are 95 to 100 percent CD4+, are MHC class II restricted, and produce gamma interferon. They proliferate in response to autologous monocytes infected with live Cowdria but not in response to uninfected monocytes. These T-cell lines will facilitate the search for Cowdria antigens that are immunogenic for T cells and will therefore be of relevance in the development of a subunit vaccine against the disease.